Um texto e muitas vozes: as crianças, o Pensar Alto em Grupo e a construção de sentidos de poemas - Marcondes, Vivian Maria (2016)
This Applied Linguistics research investigates a dialogic practice of literacy within a real context of language use called Pensar Alto em Grupo (Groupthinking Aloud) (ZANOTTO, 1992; 1995; 2014). Pensar Alto em Grupo (Groupthinking Aloud) aims to train active-responsive readers (BAKHTIN, 2011), who build meanings from texts in situations of collective reasoning (PONTECORVO, 2005), considering the manifold readings that a single text allows, as well as the dialogic character of language (BAKHTIN, 2011). The justification for this research lies in the need of meditation upon the reading practices adopted at schools, which tend towards “didactizing” reading by using texts as a framework to teach grammar and orthography or to transcribe information therein contained (CASTRO; DIONÍSIO, 2003; REYES, 2012). But this research is also justified by the indispensability of a paradigm shift concerning this practice, with a view to adopting a new tradition that allows building meanings from a text. This is, hence, a qualitative research inserted in the interpretivist paradigm. It is an “action-research” performed with children between 9 and 10 years old enrolled on the 5th grade of an elementary private school in the Zona Oeste (West Zone) of São Paulo – this is the group with which I worked as a mediator-teacher. Based on the readings of previously selected poems and proposing the Pensar Alto em Grupo (Groupthinking Aloud) method to build meanings to the texts, I investigated the following questions: 1) How does the process of building meanings by the readers work when the procedure adopted is based on the Pensar Alto em Grupo (Groupthinking Aloud) method and on dialogic relationships? 2) In which aspects reading literature modifies the relationship between students/readers and poetry? 3) Which actions and interventions by the teacher or mediator promote the reader’s development? Theoretical foundation is related to the processes of alphabetization, literacy (individual and social dimensions), and practices of literacy (monologic and dialogic). The data generation took place after four encounters in which Pensar Alto em Grupo (Groupthinking Aloud) reading method was adopted. The results revealed the following: 1) The reading process based on dialogism and on verbal interaction allows a better understanding of the texts. 2) Reading literature and building collective meanings from it develop a reading curiosity and the fondness for reading; doing so also demystifies the idea that the didactic end of this activity is its only purpose. 3) In the light of the texts that were read and collectively discussed, the reader establishes interdisciplinary and intertextual relations, improving her comprehension about them, and improves her literary repertoire and general knowledge. 4) The teacher or mediator needs to transform the occupation itself into an object of meditation, with a view to reflecting on the propositions and interventions that contribute towards he constitution of a literary reader